Optimalisasi Fungsi Masjid sebagai Sarana Pendidikan Islam dalam Menyelesaikan Krisis Spiritual Remaja di Banda Aceh - Nisa Khairuni; Anton Widyanto (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Optimization of the masjid's functions is one of the efforts to solve teenage spiritual crisis in Banda Aceh Municipality. This study aimed to investigate several concerns as the following: the position and functions of masjid, the conditions of the teenage spiritual crisis, and the optimization of masjid as an Islamic education facility in Banda Aceh.The study used the qualitative method. Data were collected by observation, interview, and documentation. The results of the study showed that masjid in Banda Aceh has become the center of Muslim community activities in terms of religious and educational affairs, among others (i.e., worship place). The teenagers in Banda Aceh have mostly faced spiritual crises such as ignoring adhan (calling for prayers), neglecting congregated payers, not performing any prayer at all, and being busy with activities. These issues were highly likely to be influenced by drugs, illegal racing, wasting time in coffee shops, and immoral behaviors (i.e., free sex). Therefore, masjid as an important Islamic education center has been optimized through several ways, two of which included regular Islamic learning groups and teenagers' activities under the coordination of the masjid.